Analisis Latensi Video Streaming Antara Jaringan Berbasis Local Area Network dan Web - Unang Achlison; Joseph Teguh Santoso; Khoirur Rozikin; Fujiama Diapoldo (STEKOM PRESS, 2022)
The current era is growing Live streaming which includes audio and video data. This research method collects data through the results of measuring Video Streaming latency (delay time) on variations of Local Area Network and Web-based computer networks. Based on the analysis of measurement results, the latency value (delay time) of Video Streaming on Local Area Network-based devices using Quality of Service (QoS) obtained a value of 8.58 ms and is smaller (optimal) compared to Web-based networks. Keywords : Quality of Service, latency, LAN, Web